Quantile relationship between financial development, income, price, CO2 emissions and renewable energy consumption: evidence from Nigeria - Somoye, Oluwatoyin Abidemi; Seraj, Mehdi; Ozdeser, Huseyin; Mar’I, Muhammad (Letters in spatial and resource sciences, 2023)
One of the solutions to climate change is the adoption and use of renewable energy sources. This understanding has driven Nigerian stakeholders to set a goal of achieving net–zero emissions by 2060. Capitalizing on the limitations of existing literature, this study employs a Quantile–on–Quantile (QQ) and quantile regression approach to investigate the impact of financial development on renewable energy consumption in Nigeria from 1960–2018. In addition, this research uses GDP per capita, energy price, and CO 2 emissions as moderating variables to eliminate omitted variable bias. The outcome of the QQ technique showed that financial development supplies mixed shocks (positive and negative) to renewable energy consumption. The negative shocks are highly negative. The quantile regression result also showed that financial development influences renewable energy consumption negatively at the lower quantile (0.10–0.20) and the upper quantile (0.80–0.90). The policy implications are discussed for Nigeria.